Ukrainian cuisine and drinks in cultural space: from ritual symbolism to global presentation - Polyovyk, Volodymyr; Matyushenko, Raisa (Вісник гуманітарних наук, 2026)
The article presents a comprehensive culturological analysis of Ukrainian cuisine as a multidimensional phenomenon of intangible cultural heritage that accumulates historical experience, ethnic memory, collective ideas and symbolic meanings of the Ukrainian people. Ukrainian cuisine is interpreted as an important marker of ethnocultural identity, which reflects traditional worldview models, value orientations, social norms and moral and ethical principles formed in the process of long-term historical development. The study analyzes the ritual, everyday and regional dishes of Ukrainians in the context of their semantics, symbolic codes, historical continuity and functioning in the system of traditional culture, which allows us to trace the relationship of gastronomic practices with mythological representations and the social structure of society. It is substantiated that traditional dishes within the framework of ritual actions perform not only a utilitarian function of ensuring life, but also a deep symbolic and communicative role, acting as a means of sacralizing space and time and a form of non-verbal cultural communication. The regional mosaic of the gastronomic tradition of Ukraine is studied, which is manifested in the variability of ingredients, cooking technologies and local interpretations of dishes, in particular borscht, as a key cultural concept that unites different regional identities within the national cultural space. The role of Ukrainian cuisine in preserving collective memory is shown. Special attention is paid to the analysis of the representation of Ukrainian cuisine in the foreign gastronomic space, as well as the growing popularity of Ukrainian culinary heritage as a component of cultural diplomacy. It is believed that the foundation of Ukrainian culinary traditions was laid more than 7 thousand years ago by the Trypillians. It was then that our ancestors learned to make bread, which for millennia became the "head of everything". The symbol of Ukrainian cuisine from ancient times to the present day is borscht, which CNN included in the 20 most delicious soups in the world. Our ancestors gave borscht a sacred meaning, because they believed that with its steam the souls of the dead flew to heaven. Therefore, borscht was an obligatory dish at memorial dinners, both in the past and in our time. In conclusion, it is argued that Ukrainian cuisine functions not only as a food system, but as a complex cultural code that represents the ethnic history, symbolic structures, and identity of the Ukrainian people in a globalized world.